The Urgency of Indonesia Government to Dealing with Mercatilism from Developed Country - Navalino, R Djoko Andreas; Sumartono Sumartono; Wildan Akbar Hashemi Rafsanjani (HM Publisher, 2021)
This research is based on fact that with the global economic every people have a chance to cooperation with other. In that condition, the government of Indonesia are still ignorant with danger and impact of mercatilism. Prevention and regulation to face the mercatilism still appear unthinkable. The purpose of this research is to develop the awareness of the government of Indonesia towards prevention practice mercatilism in indonesia by reaching complete comprehension. The main object is the regulation to prevent mercatilsm from develope country to maintain sovereignty. This qualitative descriptive reasearch is based on fact and observation with literation as adjunct. The results of this research are expected to obtain insights to the government in establishing efficient policy related to economy management in advance, both in preventing and face of the mercatilism. This research expects awareness from the government toward the danger of mercatilism for develompent country and capability of the government in managing policies in economy related with mercatilism.